2004
DOI: 10.1177/1359104504043918
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Parental Engagement in a Community Child and Adolescent Mental Health Service: A Qualitative Comparison of Completers and Non-Completers

Abstract: A B S T R A C TAttrition is a significant problem in child mental health services. Research investigating the factors associated with attrition has produced conflicting results, and failed to consider clients' own decision to terminate treatment prematurely. This study investigated parental accounts of why they completed or discontinued treatment. Completers and non-completers were interviewed using an open-ended interview schedule. All completed the Strengths and Difficulties Questionnaire (SDQ) before beginn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 23 publications
1
40
1
3
Order By: Relevance
“…Although the latter indicated that generic standardized measures were useful in making decisions about priority, they should be selected to reflect specific service objectives or in combination with specific or tailor-developed instruments. Other interesting characteristics of these studies were the frequent combination of quantitative and qualitative measures [15,40,45], and the repeated completion of the SDQ at follow-up intervals, ranging from a few weeks to 3 years.…”
Section: Use With Children With Physical and Developmental Disordersmentioning
confidence: 99%
“…Although the latter indicated that generic standardized measures were useful in making decisions about priority, they should be selected to reflect specific service objectives or in combination with specific or tailor-developed instruments. Other interesting characteristics of these studies were the frequent combination of quantitative and qualitative measures [15,40,45], and the repeated completion of the SDQ at follow-up intervals, ranging from a few weeks to 3 years.…”
Section: Use With Children With Physical and Developmental Disordersmentioning
confidence: 99%
“…As federal and state dollars spent on researching parent training programs are being invested with the expectation that the programs will eventually be turned over to and used by community providers, it is imperative that community providers understand common participation barriers and are equipped with techniques that can be used to increase engagement. Unfortunately, while some barriers to participation in community-run interventions have been identified, there is still much unknown about the various obstacles faced by families that are preventing them from achieving optimal results (Attride-Stirling, Davis, Farrell, Groark, & Day, 2004; Baker-EriczĂ©n, Jenkins, & Haine-Schlagel, 2013). More importantly, minimal research has been conducted on specific methods and alternatives to improve parental attendance and high quality participation (Ingoldsby, 2010; Nock & Ferriter, 2005; Nock & Kazdin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Completers also identified factors that facilitated their involvement in treatment (i.e. parenting differently) and, indicated fewer obstacles than non-completers (Attride-Stirling, Davis, Farrell, Groark, & Day, 2004). Evidence also suggests that compared to families who remain in treatment, parents who terminate services prematurely are more likely to report situational obstacles (e.g., additional life stressors, lack of resources) (Prinz & Miller, 1994).…”
Section: Introductionmentioning
confidence: 99%